PENGEMBANGAN KOMPONEN-KOMPONEN KURIKULUM BARU PAI PADA KMA 183 dan 184 TAHUN 2019 - Djahuno, Ridwanto (LP2M IAIN Sultan Amai Gorontalo, 2023)
The purpose of this study is to describe the components of pai curriculum development. Education can not be separated from the name of learning tools, and learning devices are organized in a curriculum. Because the curriculum is a set of subjects and educational programs provided by an educational institution that contains the design of lessons that will be given to students in one period of education. In the curriculum there are components of kurikum development that can create education in a better direction, Good education is an education that has a directed purpose, the content / material of the lesson can be received by students so that the knowledge in the trasfer by educators can be absorbed, methods / strategies that are done can achieve the desired goals, and in eveluasis either before, moderate, or after the education process is running. The motto used in this study is qualitative research method with documentation method. For data sources the author obtained from the library with data collection techniques using the finding technique. the result of this study is the application of pai curriculum components in every PAI learning.